Global burden and projections of stroke and its subtypes attributable to high alcohol use during 1990–2021: insights from the global burden of disease study 2021 - Zhan, Fangfang; Chen, Yifan; Qiu, Hong; Chen, Yimin; Lin, Shuping; Zhan, Liqiong; Ni, Jun (Frontiers in Neurology, 2025)
BackgroundStroke represents a critical public health challenge with far-reaching global implications for human health. In this study, we seek to characterize the global trends in the burden of stroke attributable to high alcohol use from 1990 to 2021 and investigate its associations with socioeconomic status.MethodsData on the burden of stroke attributable to high alcohol use were derived from the Global Burden of Disease (GBD) study. The main evaluation indicators include mortality, disability-adjusted life years (DALYs), age-standardized mortality rates (ASMR), and age-standardized DALY rates (ASDR). Trends in disease burden across genders, age groups, and regions were analyzed. Decomposition, frontier, and forecasting analyses were also conducted for the disease.ResultsIn 2021, stroke attributable to high alcohol consumption remain a substantial global health burden, accounting for 253,625 deaths (95% UI: 53,445–506,300) and 6,003,243 DALYs (95% UI: 1,323,435–11,423,164) worldwide, respectively. ASMR and ASDR for stroke attributable to high alcohol consumption show a global decline, with an EAPC of −1.81 (95% CI: −1.88 to −1.75) for ASMR and −1.63 (95% CI: −1.70 to −1.56) for ASDR. Findings reveal that in global, high, high-middle and middle SDI regions, epidemiological changes are the primary drivers of decline in mortality and DALYs for disease burden. By 2030, the ASMR for high alcohol use-attributable stroke is projected to decline from 4.3 per 100,000 in 2021 to 4.15 per 100,000, while the ASDR is forecast to decrease from 98 per 100,000 in 2021 to 95 per 100,000.ConclusionIn summary, ASMR and ASDR for stroke attributable to high alcohol consumption decline globally, and in most regions from 1990 to 2021. Relevant countries and institutions should continue to attach great importance to the impact of this disease and formulate targeted policies.